PENGARUH MOTIVASI DALAM MENINGKATKAN DISIPLIN KERJA KARYAWAN PADA PT. PLANET ARTHA INDONESIA CABANG MUARA ENIM - Hertanudin Hertanudin (Sekolah Tinggi Ilmu Ekonomi YPPI Rembang, 2020)
This research aims to find out the influence of motivation to improve the work discipline of the employees in Muara Enim branch of PT. Planet Artha Indonesia. The data used in the research is primary and secondary data. The primary data were taken by interview, observation, and questioners, while the secondary data were taken from company’s documents and guiding books used to support this research. The sampling technique used is saturated sample, as many as 66 people. Analysis technique used in this research is simple linier regression analysis. The research result shows that variable motivation has positive influence on the work discipline of employees in Muara Enim branch of PT.Planet Artha Indonesia. The coefficient test result shows that 41,1% motivation variables are able to explain the variation of employees discipline work variable, while 58,9% are stated by other variables without including the research model.